The Relationship of Family Support with Adherence in Diabetes Mellitus Patients in the Working Area of the Barong Tongkok Public Health Center District West Kutai - Lilis Kumalawati (Jurnal KESANS : Kesehatan dan Sains, 2023)
Background: Diabetes Mellitus (DM) is the number 4 health problem in the world. Data from the International Diabetes Federation 2019 estimates that there are 463 million people (aged 20-79 years) suffering from DM. According to Riskesdas at 2018 47.2% of sufferers have poor control of their blood sugar.  Objective: To determine the relationship between family support and diet compliance of Diabetes Mellitus patients in the working area of the Barong Tongkok Health Center, West Kutai Regency.  Methods: The research design in this study is descriptive correlation using a cross-sectional approach. Determination of the sample using non-probability sampling, the research sample amounted to 78 respondents. Results and Discussion: Family support in the sufficient category (59.0%), Diabetes Mellitus Dietary adherence in the non-adherent category (62.8%). The relationship between family support and Diabetes Mellitus Diet was obtained p-value = 0.002.  Conclusion: There is a relationship between family support and diet compliance of Diabetes Mellitus patients in the working area of the Barong Tongkok Health Center, West Kutai Regency